La pénétration des adhésifs de doublage - Manon D’haenens (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The reversibility of linings is complex and intimately linked to the penetration of adhesives into the original canvas. The aim of the research was to define factors of influence as well as to develop a method to assess adhesive penetration. The adhesives tested are currently the most frequently used: Plextol® B500 and Beva® 371.